Закон монолита: [фантастический роман] / Дмитрий Силлов - Силлов Дмитрий Олегович (Сталкер, 2017)
Экземпляры: Аб (20181230) / Инвентарный номер: 45770 / Цена: / Авт.знак: С 36 / ГРНТИ: 17.82.31 / ББК: 84(2Роc=Рус)6-445